التكنولوجيا الرقمية والابتكار التكنولوجي وأثرهما على النمو الاقتصادي: دراسة تحليلية مقارنة بين الدول المتقدمة والنامية (2020–2025) (مجلة العلوم الشاملة, 2025)
This study aims to analyze the impact of digital technology and technological innovation on economic growth through a comparative analysis between advanced economies (United States, Germany, Japan) and developing countries (India, Egypt, Nigeria) during the period 2020–2025. The research adopts a descriptive comparative methodology supported by advanced statistical tools such as Pearson correlation matrix and ANOVA tests. Findings reveal a significant innovation gap between advanced and developing countries, with the former scoring an average of 85.67 in the Global Innovation Index compared to 39.67 for the latter. Investment in R&D reached 3.30% of GDP in advanced economies versus only 0.70% in developing ones. Although developing countries achieved higher economic growth rates (4.40% vs. 2.17%), this growth lacks sustainability, as advanced economies recorded sustainability indices 45% higher. The results highlight that sustainable growth requires strong investments in innovation and R&D rather than short-term rapid expansion.
Keywords: الابتكار التكنولوجي، النمو الاقتصادي، التكنولوجيا الرقمية، الاستدامة، البحث والتطوير، الفجوة الابتكارية